Tecendo sustentabilidade: plano de manejo participativo da “taboa” (Typha domingensis Pers.), no Parque Estadual Serra Do Mar – Núcleo Picinguaba, Ubatuba, SP, Brasil - Sauini, Thamara [UNIFESP] (2023)
Traditional communities that live and use the natural resources present in Conservation Units must have a Management Plan, a technical document prepared especially to manage the resources of these areas. In this context, there is Quilombo da Fazenda, a community located in a protected area, which uses the cattail plant (Typha domingensis Pers. - Typhaceae) to make handicrafts and generate local income; and that requested a Management Plan to comply with the law. Therefore, the objective of this work was to prepare documents with recommendations for good management practices for the sustainable extraction of cattails, in order to guide and regulate the extraction of this plant among the residents of Quilombo da Fazenda in an area of the Serra do Mar State Park, and , also, residents of other UCs and/or protected areas. Furthermore, this work aimed to promote the participation of local quilombolas in all stages of their development, register artisans who extract cattails, evaluate the technique of traditional extraction and processing of cattails to define an ecological, socially and economically sustainable model for activity, and generate scientific data that would support the legal extraction and commercialization of handicrafts. Thus, using the methodology of participatory ethnobotanical research, the study included the active participation of the residents of Quilombo da Fazenda, in all stages of its implementation. To define a viable Management Plan, the following aspects were considered: i) Ecology of the cattail, through a bibliographical review of the literature and the understanding of the characteristics, interactions and functioning of the cattail and the environment as a whole; ii) Zoning of the plant area and species that co-occur in the taboal area, aiming at conservation priorities and local management needs; iii) Traditional extraction and processing, for the understanding and use of local management in this participatory research; iv) Social and economic aspects, since the plant is used to generate local income within the community; and v) Scientific data, considering that it is necessary to ensure that the biomass stock of the extracted resource is maintained, meeting the bases of sustainability. To estimate cattail biomass, it was found that the ideal size of the sample plot is 2m x 2m and that the most appropriate variable to be measured and that best relates to the Wet Weight and Dry Weight of the cattail is the “height of the tallest leaf”. high of the cap”. It was seen that cattails have a high capacity for regeneration and that traditional management is a good treatment for the area, as it can be reproduced, guaranteeing the sustainability of the resource. The participation of quilombolas was fundamental for the development of this study, for the management and elaboration of regulations on the use of local resources, for the promotion of local development based on the sustainable use of cattails and consequently for the conservation of the area where they are located. The study contributed to enabling the extraction and trade of this plant, through the sustained production and sale of handicrafts; for the appropriation of the benefits of natural resources by the community, with the establishment of policies aimed at socio-environmental planning, with the conservation of the biological and cultural diversity of the Atlantic Forest, as it will guide the extraction of this plant among residents of Quilombo da Fazenda, and also residents of other conservation units and/or protected areas.